UAV thermal orthomosaics from Fuglebekken and Ariebekken (June, July and September 2022-2023) from the vicinity of the Polish Polar Station Hornsund, Spitsbergen, Svalbard - Abhishek Bamby Alphonse; Tomasz Wawrzyniak; Nicole Hanselmann; Marzena Osuch (PANGAEA, 2024)
The rapidly changing climate in the High Arctic region is posing significant challenges to its ecosystem. To better understand the changes, this study utilises Uncrewed Aerial Vehicle (UAV) technology equipped with a thermal camera to investigate ground and water temperatures in the catchments of southwest Spitsbergen. This approach provides high-resolution, real-time data, offering a detailed understanding of surface temperatures in this remote and harsh environment. Integrating UAV technology with in-situ measurements enables data collection at high spatial and temporal scales, facilitating a thorough analysis of temperature trends and patterns. The research introduces a new processing workflow using open-source packages to create thermal orthomosaics, which enhances the accuracy and efficiency of the analysis. The final developed orthomosaics, with a spatial resolution of 5cm, examine spatial variations in ground temperature and explore factors influencing land and water surface temperatures. Additionally, it investigates thermal patterns in Arctic hydrological systems, such as channels and ponds, allowing for identifying and characterising flow paths in the catchments, including groundwater intrusions and surface water mixing. This multidimensional approach aims to provide valuable insights into the complex interactions between cryo-, hydro-, and meteorological dynamics in the High Arctic.